EVALUATION OF EFFICACY OF FORMALIN TREATED M YCOPLASMA GALLISEP'fICUM VACCINE IN BROILER CHICKENS (Biological Sciences - PJSIR, 2002)
To minimize the local problem of Mycoplasma gallisepticum (MG) the potential of two indigenous MG isolates (MI- 203 and MI-211) was utilized for vaccine development. Formalin treated vaccines were developed and efficacy was evaluated in female broiler chickens (Cobb). Both the vaccines were found effective in providing protection against MG S6_ challenge that caused 11.5 to 23.3% body weight losses as compared to negative control as well as vaccinated cluckens. Besides t_hese i nactivated vaccines, the effectiveness of MG-F Jive vaccine was compared with that of mact1vated test vaccmes. MG-F Jive vaccine expressed its seemingly low pathogenic character by exhibiting 5.5 to 9.3% reduced body weight gain as compared to control chickens. The study suggests that vaccines prepared from local ISOiates (MI-203 and MI-211) are effective in providing protection against challenge with MG-S6 by providing better growth rate and total body weight gain , feed uptake and conversion efficiency, eliminating morbidity and keeping chickens infection free.